Age‐Related Vascularization and Ossification of Joints in Children: An International Pilot Study to Test Multiobserver Ultrasound Reliability. Issue 4 (27th March 2020) - Windschall, Daniel; Collado, Paz; Vojinovic, Jelena; Magni‐Manzoni, Silvia; Balint, Peter; Bruyn, George A. W.; Hernandez‐Diaz, Cristina; Nieto, Juan Carlos; Ravagnani, Viviana; Tzaribachev, Nikolay; Iagnocco, Annamaria; D'Agostino, Maria Antonietta; et al.
Abstract : Objective: To determine the intra‐ and interobserver reliability of ultrasound (US)‐detected age‐related joint vascularization and ossification grading in healthy children. Methods: Following standardized image acquisition and machine setting protocols, 10 international US experts examined 4 joints (wrist, second metacarpophalangeal joint, knee, and ankle) in 12 healthy children (divided into 4 age groups: 2–4, 5–8, 9–12, and 13–16 years). Gray‐scale was used to detect the ossification grade, and power Doppler ultrasound (PDUS) was used to detect physiologic vascularization. Ossification was graded from 0 (no ossification) to 3 (complete ossification). A positive PDUS signal was defined as any PDUS signal inside the joint. Kappa statistics were applied for intra‐ and interobserver reliability. Results: According to the specific joint and age, up to 4 solitary PDUS signals (mean 1.5) were detected within each joint area with predominant localization of the physiologic vascularization in specific anatomic positions: fat pad, epiphysis, physis, and short bone cartilage. The kappa values for ossification grading were 0.87 (range 0.85–0.91) and 0.58 for intra‐ and interobserver reliability, respectively. The bias‐adjusted kappa values for intra‐ and interobserver reliability were 0.71 (range 0.44–1.00) and 0.69, respectively. Conclusion: Detection of normal findings (i.e., grading of physiologic ossification during skeletal maturation and identification of physiologic vessels) can be highly reliable by using clear definitions and a standardized acquisition protocol. These data will permit development of a reliable and standardized US approach for evaluating pediatric joint pathologies.